The changing epidemiology of syndactyly in Chinese newborns: a nationwide surveillance-based study - Zhi-Yu Chen; Wen-Yan Li; Wen-Li Xu; Yu-Yang Gao; Zhen Liu; Qi Li; Bin Yu; Li Dai (BMC, 2023)
Abstract Background Little is known about the epidemiologic features of syndactyly (SD) in Chinese newborns. Methods Using 2007-2019 data from the Chinese Birth Defects Monitoring Network, we conducted a prevalence analysis on overall, isolated and associated syndactyly according to birth year, maternal age, maternal residence, geographic region and infant sex, with special interests in time trends, perinatal outcomes and clinical phenotypes. Results A total of 13,611 SD cases were identified among 24,157,719 births in the study period, yielding the prevalence of 5.63, 4.66 and 0.97 per 10,000 for overall, isolated, and associated SD, respectively. The prevalence of each type of SD exhibited an upward trend over the period. The prevalence of overall SD varied significantly by maternal residence (urban vs. rural, 6.69/10,000 vs. 4.35/10,000), maternal age (< 20 years, 5.43/10,000; 20-24 years, 5.03/10,000; 25-29 year, 5.65/10,000; 30-34 years, 6.07/10,000; ≥ 35 years, 5.76/10,000), geographic region (central, 5.07/10,000; east, 6.75/10,000; west, 5.12/10,000), and infant sex (male vs. female, 6.28/10,000 vs. 4.86/10,000). Newborns with associated SD were more likely to be born prematurely (29.2% vs. 10.6%) or with low birthweight (30.5% vs.9.8%) than those with isolated SD. The bilaterally, and unilaterally affected cases accounted for 18.4% and 76.7%, respectively. The feet were more frequently involved (64.3%) in those bilaterally affected cases, while right side preference (right vs left: 53.8% vs 46.2%) and upper limbs preference (hand vs foot: 50.8% vs 48.0%) were found in unilateral cases. Conclusions The prevalence of syndactyly in China is on the rise and notably higher than that in other Asian and European countries, highlighting the importance of investigating the etiology, epidemiology, and clinical implications of this condition in the Chinese population.